Pendidikan Karakter Dengan Pendekatan Tasawuf Modern Hamka dan Transformatif Kontemporer - Sofyan Rofi; Benny Prasetiya; Bahar Agus Setiawan (UMSU, 2019)
This article was written to provide an overview of Character Education with Modern Hamka and Contemporary Transformative Sufism Approaches. The construction of Hamka Sufi thought is very important for the world today, not only for reforming Islamic thought but also for reconstructing modern spirituality. Modern Sufism for Hamka is the application of qanaah, sincerity, and motivation to work Buya Hamka's character education perspective is that the nature of every human being basically leads to always do good and submit to his Khaliq.